A descriptive examination of homicide and the victim-offender overlap - Butler, H. Daniel (Routledge handbook of homicide studies, 2024)
Criminological research regularly draws attention to offending and victimization, referred to as the victim–offender overlap. A variety of perspectives are provided to understand this relationship, such as routine activities and lifestyle perspectives, control perspectives, and social interactionist perspectives. In this chapter, we provide an overview of these perspectives and research on homicide offending. We then provide a descriptive analysis of the victim–offender overlap as it relates to homicide offending. We use the 2004 Survey of Inmates in State and Federal Correctional Facilities to examine differences between persons incarcerated for homicide offenses as compared to non-homicide offenses. The findings reveal that non-homicide offenders are more likely to self-report extensive criminal histories than homicide offenders, but that homicide offenders are more likely to report histories of victimization. We conclude with implications for theory and policy in addition to highlighting the need to better understand the lived experiences of homicide offenders.